2012
DOI: 10.1021/es300754p
|View full text |Cite
|
Sign up to set email alerts
|

Emission Characteristics of Heavy Metals and Their Behavior During Coking Processes

Abstract: Besides organic pollutants, coke production generates emissions of toxic heavy metals. However, intensive studies on heavy metal emissions from the coking industry are still very scarce. The current work focuses on assessing the emission characteristics of heavy metals and their behavior during coking. Simultaneous sampling of coal, coke, residues from air pollution control devices (APCD), effluent from coke quenching, and fly ash from different processes before and after APCD has been performed. The total hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Coke-oven workers are a typical population generally exposed to a mixture of contaminants, such as polycyclic aromatic hydrocarbons (PAHs), which are the major pollutants released from incomplete combustion of coal (Mu et al, 2012;Passant et al, 2002). Coal also contains trace amounts of metallic elements released during carbonization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coke-oven workers are a typical population generally exposed to a mixture of contaminants, such as polycyclic aromatic hydrocarbons (PAHs), which are the major pollutants released from incomplete combustion of coal (Mu et al, 2012;Passant et al, 2002). Coal also contains trace amounts of metallic elements released during carbonization.…”
Section: Introductionmentioning
confidence: 99%
“…Coal also contains trace amounts of metallic elements released during carbonization. These elements often include toxic heavy metals, especially arsenic (As), cadmium (Cd), chromium (Cr), nickel (Ni), and lead (Pb) (Mu et al, 2012;Passant et al, 2002). The carcinogenic potential of these heavy metals has been widely Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/envres studied in humans and experimental animals ('t Mannetje et al, 2011;Boffetta et al, 2011;Huang et al, 2004;Joseph, 2009;O'Brien et al, 2003;Oller, 2002;Verougstraete et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This supply is mainly attributed to the traditional biomass using for heating and cooking in rural areas of developing countries (Demirbas, 2005). However, many studies have been reported that the traditional heating and cooking processes may result in low energy efficiency and high gaseous pollutant emissions during incomplete combustion (Freeman and Cattell, 1990;Mu et al, 2012;Vuthaluru, 2004;Williams et al, 2012). Therefore, the co-combustion of biomass with coal for electricity production has received fairly intensive studies, and suggested that the thermochemical reactivity and combustion properties could be promoted by addition of suitable proportion of biomass (Gil et al, 2010;Goldfarb and Liu, 2013;Haykiri-Acma et al, 2006;Idris et al, 2012;Masnadi et al, 2014;Vamvuka et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Coking is a dry distillation process in oxygen-free conditions at high temperatures (Mastral and Callén, 2000). The contaminants emitted during coking include inorganic compounds, heavy metals, OC, and EC (Tsai et al, 2007;Mu et al, 2012;Liu et al, 2013;Mu et al, 2013;Liu et al, 2014). Coke-plant workers are exposed to organic pollutants, leading to high lung cancer mortality (Redmond, 1983;Bertrand et al, 1987).…”
Section: Introductionmentioning
confidence: 99%